2010
DOI: 10.3109/17538150903358784
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the frequency of online health information seeking: Results of a Web-based survey conducted in France in 2007

Abstract: In the general population, social disparities in Internet practices have been less described than disparities in health information access. Aim is to determine whether there are differences in the frequency of Internet use for health information among health seekers. We conducted an Internet-based survey from November 2006 to March 2007. We considered the 3720 residents of France who had searched for health information during the previous 12 months. This study reveals different uses of the Internet for health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
49
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 37 publications
12
49
2
3
Order By: Relevance
“…When it comes to health, women seem to be more engaged, more involved, more attentive and apparently better informed decision-makers. Thus, gender plays an important role in the patterns of health information behaviour of the Finnish citizens in the ages from 18 to 65 years; a result which is in line with previous research internationally (Rakowski et al, 1990;Kassulke et al, 1993;O'Keefe et al, 1998;Renahy and Chauvin, 2006;Rice, 2006;Lorence and Park, 2007;Renahy et al, 2010;Wellstead, 2011). These revealed differences in gender-related health information behaviour likely affect health behaviour and status, and may account for a considerable part of the still enduring life expectancy gap between Finnish men and women as well.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…When it comes to health, women seem to be more engaged, more involved, more attentive and apparently better informed decision-makers. Thus, gender plays an important role in the patterns of health information behaviour of the Finnish citizens in the ages from 18 to 65 years; a result which is in line with previous research internationally (Rakowski et al, 1990;Kassulke et al, 1993;O'Keefe et al, 1998;Renahy and Chauvin, 2006;Rice, 2006;Lorence and Park, 2007;Renahy et al, 2010;Wellstead, 2011). These revealed differences in gender-related health information behaviour likely affect health behaviour and status, and may account for a considerable part of the still enduring life expectancy gap between Finnish men and women as well.…”
Section: Discussionsupporting
confidence: 76%
“…It has also been observed that men, due to gender role strains and social constructions of masculinity, tend to be unaware of sources of health-related information and have inadequate competency to search for them because of either pure ignorance or reluctance, and accordingly low motivation, of seeking out what they do know to be available (Dean, 1989;Pleck, 1995;Courtenay, 2000;Wellstead, 2011). Research, both prior to the Internet (Weisman and Teitelbaum, 1989;Rakowski et al, 1990;Kassulke et al, 1993;O'Keefe et al, 1998) and since the Internet appeared (Ek, 2005;Renahy and Chauvin, 2006;Rutten et al, 2006;Lorence and Park, 2007;Renahy et al, 2010), that have specifically examined gender as a variable in health information seeking behaviour also clearly demonstrates that women are more active seekers of health-related information than men. Rice (2006) analysed seven major US nationally representative data sets from the Pew Internet and American Life Project and found that one of the strongest and most consistent predictors of frequent health information seeking was being female.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Being female is among the strongest predictors of conducting OHISB [15,48,49]. Whereas women report to be more interested in health information and show more active search activities [56], men are less likely to read health information [57].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that only mother's education (and not the father's) was significantly associated with HISB suggests that gender may also play a role in shaping HISB in young adults. Scholars have proposed that in most Western cultures, women have a 'nurturing' role that makes them more likely to seek health information on behalf of their family (Renahy et al, 2010, Ek, 2015. Our results, however, cannot tell us whether those who have more educated mothers and declared seeking only their family are not able to seek additional sources when necessary.…”
Section: Discussionmentioning
confidence: 60%